2021
DOI: 10.1186/s40478-021-01220-8
|View full text |Cite
|
Sign up to set email alerts
|

Mouse closed head traumatic brain injury replicates the histological tau pathology pattern of human disease: characterization of a novel model and systematic review of the literature

Abstract: Traumatic brain injury (TBI) constitutes one of the strongest environmental risk factors for several progressive neurodegenerative disorders of cognitive impairment and dementia that are characterized by the pathological accumulation of hyperphosphorylated tau (p-Tau). It has been questioned whether mouse closed-head TBI models can replicate human TBI-associated tauopathy. We conducted longitudinal histopathological characterization of a mouse closed head TBI model, with a focus on pathological features report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 77 publications
3
24
2
Order By: Relevance
“…Previous studies using repetitive models of TBI have demonstrated a similar trend of shortened loss of righting reflex times after successive injuries. 69 In our study, no significant body weight differences between groups were observed at baseline. However, body weight decreased after each successive injury for both sham and TBI mice but began to recover 48 hours following the third and final hit.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies using repetitive models of TBI have demonstrated a similar trend of shortened loss of righting reflex times after successive injuries. 69 In our study, no significant body weight differences between groups were observed at baseline. However, body weight decreased after each successive injury for both sham and TBI mice but began to recover 48 hours following the third and final hit.…”
Section: Discussioncontrasting
confidence: 56%
“…TBI often causes severe paralysis or intellectual impairment in patients, with high rates of injury, disability and mortality [2]. The mechanism of injury includes multiple cascade-events, such as the release of excitatory toxic molecules, metabolic challenges, inflammation and apoptosis, accompanied by the destruction of the blood-brain barrier (BBB) and cell swelling, which eventually leads to cell death [3]. There has been no effective treatment strategies for TBI to date, though increasing attention has been paid to TBI.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of tau neuroimaging as a predictor in preclinical and prodromal stages of AD remains uncertain ( 106 ). Moreover, the presence of tau binding in mild TBI ( 107 ), FTD, PSP, and several other degenerative disorders clouds the picture further.…”
Section: Combining Perfusion Spect Scans With Other Modalities For Im...mentioning
confidence: 99%